“Quality over quantity:” smaller, targeted lesions optimize quality of life outcomes after MR-guided focused ultrasound thalamotomy for essential tremor - Buch, Vivek P.; Purger, David; Datta, Anjali; Wang, Allan; Barbosa, Daniel; Chodakiewitz, Yosefi; Lev-Tov, Lior; Li, Chelsea; Halpern, Casey; Henderson, Jaimie; McNab, Jennifer A.; Bitton, Rachelle R.; et al. (Frontiers in Neurology, 2024)
Introduction MRI-guided focused ultrasound (MRgFUS) thalamotomy of the nucleus ventralis intermedius (VIM) has emerged as a powerful and safe treatment modality for refractory essential tremor. While the efficacy of this technique has been extensively described, much remains unclear about how to optimize MRgFUS for patient quality of life (QoL), which may depend as much on a patient’s adverse effect profile as on the magnitude of tremor suppression. Diffusion tensor imaging (DTI) has been used to help guide targeting strategies but can pose certain challenges for scalability. Methods In this study, we propose the use of a simplified patient-reported change in QoL assessment to create an unbiased representation of a patient’s perception of overall benefit. Further, we propose a large-sample-size, high-resolution, 7 T DTI database from the Human Connectome Project to create a normative tractographic atlas (NTA) with representations of ventral intermediate nucleus subregions most likely to be structurally connected to the motor cortex. The NTA network-based hotspots are then nonlinearly fitted to each patient’s T1-weighted MRI. Results and discussion We found that smaller lesion size and higher extent to which the lesion is within the NTA hotspot predicted patients’ change in QoL at last follow-up. Though long-term change in clinical rating scale for tremor (CRST) impacted QoL, neither intraoperative tremor suppression nor the patient’s long-term perception of tremor suppression correlated with QoL. We provide an intraoperative threshold for accumulated dose volume (<0.06 cc), which along with the network-based hotspot in the NTA, may facilitate an easily scalable approach to help limit treatment to small, safe yet effective lesions that optimize change in QoL after MRgFUS.